PENGARUH PENGETAHUAN AWAL, KECERDASAN EMOSIONAL DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR MATEMATIKA SISWA MADRASAH TSANAWIYAH DI KECAMATAN GALANG KABUPATEN TOLITOLI - Busra, Busra; Idris, Mustamin; Ismaimuza, Dasa (AKSIOMA : Jurnal Pendidikan Matematika, 2016)
Abstract: The Research aimed at dinding out describing the direct and indirect effects of Prior Knowledge, Emotional Quotiont, and Parents attention on students Achivement of Mathematics in MTs Galang Subdistrict Tolitoli Regency. The Population of the Research was the students MTs Galang Subdistrict, Tolitoli Regency registered in 2015/2016, consisted of 984 students. These samples are taken with probability sampling technique. The data of prior knowledge and toward the mathematics learning which using achievement test, and the data emotional quotient and parents attention are taken with questionnaire. Istrument test cover validity and reliability. Hypotesis fourth, fifth, sixth, and seventh are using double regression, with significance level α = 0,05. The research findings indicated that there were significant effect between:First prior knowledge toward themathematics learning with contribution 40,7%. Second, emotional quotient toward the mathematics learning with contribution 12,1%. Third, parents attention toward the mathematics learning with contribution 11,9%. Forth, prior knowledge and emotional quotient toward the mathematics learning with contribution 45,2%. Fifth, prior knowledge and parents attention toward the mathematics learning with contribution 43,7%. Sixth, emotional quotient and parents attention toward the mathematics learning with contribution 20,1% and Seventh, prior knowledge, emotional quotient, and parents attention toward the mathematics learning with contribution 47,4%.Keywords: prior knowledge, emotional quotiont,parents attention, toward the mathematics learning